THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, AND NET PROFIT MARGIN ON STOCK RETURNS - sumatriani, sumatriani (Pusat P2M Politeknik Negeri Batam, 2023)
The aims of this study is to simultaneously and partially test and analyze the impact of the Current Ratio, Debt to Equity Ratio, and Net Profit Margin on stock returns. This study's population consisted of 11 pharmaceutical companies registered on the Indonesia Stock Exchange between 2018 and 2022. This study's sample was determined using a purposive sampling strategy, yielding a sample of 9 pharmaceutical companies with a total of 35 observation data. Multiple linear regression analysis was employed as the analytical method. The study's findings reveal that the Current Ratio, Debt to Equity Ratio, and Net Profit Margin all have an impact on stock returns at the same time. This suggests that increasing the three variables, namely the Current Ratio and Net Profit Margin while decreasing the Debt to Equity Ratio, will enhance stock returns. The current ratio has no statistically significant impact on stock returns. The debt-to-equity ratio has no substantial effect on stock returns. Meanwhile, Net Profit Margin has a minor impact on Stock Returns. Stock returns in pharmaceutical businesses listed on the Indonesian Stock Exchange will rise as Net Present Value rises.